Climate change concerns and actions – Can provision of information motivate people to fight climate change? - Panagiota Tzamourani (Deutsche Bundesbank, 2022)
Are individuals concerned enough about climate change to change their behavior and bear additional costs as a consequence? How can they be motivated to fight climate change? A Bundesbank survey conducted between April 2020 and December 2021 shows that people are more concerned about climate change than about the state of the economy. During most of the ongoing pandemic, only the coronavirus was of a higher concern. While people who rate climate change as a serious issue are also more willing to take on additional costs to help fight climate change, providing information on ways to reduce carbon emissions further increases their willingness to do so.
Keywords: 330